(untitled) (International Conference on Computers in Education, 2020)
This study investigated student engagement in paper-based, digital 2D, and VR co- creation environments. The study utilized a quasi-experimental research design with 66 tenth- grade students in two EFL classes in northern Taiwan. The results showed insignificance of co- creation platforms for behavioral and cognitive engagement. However, VR co-creativity resulted in significance in emotional engagement, due to its novel and immersive nature. The study suggested that co-creation be a long-term project for thorough idea synthesis lest the essence and strength of co-creation be under-estimated.